PENGGUNAAN APLIKASI DIGITAL PADA KESEHATAN WANITA USIA SUBUR - Karlinda; Fitriani, Yessy (Forind Press, 2025)
The use of digital applications in the health sector is growing, including for the health of women of childbearing age. The app offers a variety of features, such as menstrual cycle monitoring, pregnancy, reproductive health, and a healthy lifestyle. This study aims to analyze the use of digital applications related to the health of women of childbearing age. This study uses a cross-sectional design and is conducted online with a sample of 251 respondents who are randomly selected. Data was collected through questionnaires that included the use of health digital applications as well as health indicators of women of childbearing age. Data analysis was carried out to see the relationship between the use of digital applications and the health status of respondents. The results of the study show that the use of digital applications has an influence on the health of women of childbearing age. Respondents who regularly use health applications reported increased understanding of reproductive health, adherence to healthy lifestyles, and ease of monitoring personal health conditions. The use of digital applications plays a role in improving the health of women of childbearing age. Therefore, further education and socialization are needed so that women of childbearing age can optimally utilize digital technology to maintain their health.